2010
DOI: 10.1016/j.ecolmodel.2010.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Identifying fishing trip behaviour and estimating fishing effort from VMS data using Bayesian Hidden Markov Models

Abstract: Recent advances in technologies have lead to a vast influx of data on movements, based on discrete recorded position of animals or fishing boats, opening new horizons for future analyses. However, most of the potential interest of tracking data depends on the ability to develop suitable modelling strategies to analyze trajectories from discrete recorded positions. A serious modelling challenge is to infer the evolution of the true position and the associated spatio-temporal distribution of behavioural states u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 34 publications
1
91
0
2
Order By: Relevance
“…When analysing noisy tracking data, an HMM that infers the animal's behavioural modes can be nested within a statespace model for the estimation of the animal's locations (Jonsen et al 2005, Jonsen et al 2007). For filtered Argos locations or very low-error GPS data, HMM assign behavioural modes directly from inferences on movement data (Franke et al 2004, Morales et al 2004, Vermard et al 2010, Walker & Bez 2010. The use of environmental covariates in the HMM inference can help in understanding how predators adapt their foraging behaviour to local environmental conditions (Morales et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…When analysing noisy tracking data, an HMM that infers the animal's behavioural modes can be nested within a statespace model for the estimation of the animal's locations (Jonsen et al 2005, Jonsen et al 2007). For filtered Argos locations or very low-error GPS data, HMM assign behavioural modes directly from inferences on movement data (Franke et al 2004, Morales et al 2004, Vermard et al 2010, Walker & Bez 2010. The use of environmental covariates in the HMM inference can help in understanding how predators adapt their foraging behaviour to local environmental conditions (Morales et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, improved estimates of fishing time may be achieved by adopting methods to reconstruct trawl tracks. Hintzen et al (2010) used a spline interpolation technique to model fishing tracks from VMS data while Vermard et al (2010) identified different fishing behaviour during fishing trips, using Bayesian hierarchical models. Moreover, the collection of additional data such as individual tow length and catches per tow would allow more detailed analysis of how fishers respond to changing prey availability.…”
Section: Discussionmentioning
confidence: 99%
“…More safely it can be improved by looking for experience in other countries ( [47] Marchal et al, p. 483) identifying best practices. It is enhanced by the use of simulation models and the development of scenarios [44,49,[55][56][57][58]. Finally, the perceptions of the fishers themselves should not be underestimated and mechanisms involving them directly in the decision-making process may also help improving the capacity of governance to look ahead.…”
Section: Improving the Capacity To Look Aheadmentioning
confidence: 99%
“…Developing participatory research-and-management processes [86] will help to better understand fleet dynamics and fishing strategies [43], to optimize time and space allocation of effort [45], or to assess the potential effect of new management strategies such as the introduction of fishing rights ( [53] Marchal et al, p. 463; [54] Hamon et al, p. 549). More studies of fishers' behaviour and motivations are needed [55,56] to improve foresight. There is a need for joint analysis of environmental and economic drivers and this requires new approaches and models including behavioural models [44,49,[55][56][57][58].…”
Section: Adjusting Effort or Capacity To The Resource Productivitymentioning
confidence: 99%